Effects of intensive lipid-lowering therapy on coronary plaques composition in patients with acute myocardial infarction: Assessment with serial coronary CT angiography. Issue 2 (August 2015) - Auscher, Søren; Heinsen, Laurits; Nieman, Koen; Vinther, Kristina Høeg; Løgstrup, Brian; Møller, Jacob Eifer; Broersen, Alexander; Kitslaar, Pieter; Lambrechtsen, Jess; Egstrup, Kenneth
Abstract: Background: Statins have been shown to possess favourable effects on the cardiovascular system with stabilization of the vulnerable plaque. We sought to assess the effects of early aggressive statin treatment on plaque composition in patients with acute myocardial infarction (AMI), using serial assessment with coronary CT-angiography (CTA). Methods: In a prospective randomized blinded endpoint trial patients with AMI were randomized to an intensive lipid lowering treatment receiving statin loading with 80 mg rosuvastatin followed by 40 mg daily or standard statin therapy according to current guidelines. Patients were assessed with CTA at baseline and after 12 months with evaluation of plaque volume and composition. Results: In total, 140 patients with AMI were randomized and plaque composition was assessed in 96 patients. In the intensive care group LDL-level was median 1.3 [0.9; 1.5] mmol/l at 12 months follow-up and 2.0 [1.7; 2.4] mmol/l in the usual care group, p < 0.001. Plaque volume increased over 12 months with 43.5 (±225.8) mm 3 in the intensive care group and 19.1 (±190.2) mm 3 in the usual care group, p = 0.57. Plaque composition changed over 12 months with an increase in total dense calcium volume by 11.1 (±39.6) mm 3, corresponding to a 23% increase, in the intensive care group and a decreased by −0.4 (±26.6) mm 3 in the usual care group, p < 0.001. Necrotic core volume increased 26.8 (±122.1) mm 3 in the intensive care group and 25.2 (±80.1) mm 3 in the usual care group, p = 0.94. Conclusions: Early aggressive lipid lowering therapy significantly increases dense calcium volume in patients with AMI. Highlights: Intensive LLT did not decrease plaque volume in patients with AMI. Intensive LLT significantly increases calcium volume in patients with AMI. Intensive LLT did not change plaque vulnerability in patients with AMI.